Pengaruh Citra Merek, Harga, Kualitas Produk dan Promosi terhadap Keputusan Pembelian (Survei Konsumen Uniqlo di Jabodetabek) - Aliyya, Munadiyya Sidqin; Nuriyah, Aminah (Universitas Batanghari Jambi, 2024)
The reason researchers chose the uniqlo brand as research in Jabodetabek is based on the very high mobility of the capital city community, requiring comfortable clothing for outdoor and indoor activities. This study was conducted to determine the effect of brand image, price, product quality and promotion on purchasing decisions of uniqlo consumers in the cities of Jakarta, Bogor, Depok, Tangerang and Bekasi. The research methodology uses a descriptive quantitative approach using multiple linear regression analysis which includes classical assumption tests, hypothesis testing and multiple linear regression analysis. Based on the results of multiple linear regression analysis, the equation purchase decision (Y) = 2.752 + 0.273(brand image) + 0.279(price) + 0.230(product quality) + 0.022(promotion) with an r square value of 0.431. The independent variable in this study only has a contribution of 43.1% to influence the dependent variable. While the other 56.9% is influenced by other factors.